2021
DOI: 10.3389/froh.2021.604565
|View full text |Cite
|
Sign up to set email alerts
|

Increased Abundance of Tumour-Associated Neutrophils in HPV-Negative Compared to HPV-Positive Oropharyngeal Squamous Cell Carcinoma Is Mediated by IL-1R Signalling

Abstract: The incidence of human papillomavirus (HPV)-associated cancer is increasing and HPV is now implicated in the aetiology of more than 60% of all oropharyngeal squamous cell carcinomas (OPSCC). In OPSCC, innate immune cells such as neutrophils and macrophages generally correlate with poor prognosis, whilst adaptive immune cells, such as lymphocytes, tend to correlate with improved prognosis. This may, in part, be due to differences in the immune response within the tumour microenvironment leading to the recruitme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 60 publications
0
10
0
Order By: Relevance
“…Interaction of IL-1β with the TME leads to monocyte recruitment that then differentiate into tumor-associated macrophages (TAMs) whose increased levels in HNSCC are associated with poor prognosis [ 12 , 117 ]. Also, stimulates the production of numerous cytokines by different cell types, such [ 116 ] as cancer-associated fibroblasts (CAFs), normal fibroblast, endothelial cells, neutrophils as well as oral dysplastic and cancer cells, among others [ 10 , 11 , 98 , 118 ], through an IL-1-dependent innate immune response.…”
Section: Il-1 Signaling In Head and Neck Squamous Cell Carcinomamentioning
confidence: 99%
See 2 more Smart Citations
“…Interaction of IL-1β with the TME leads to monocyte recruitment that then differentiate into tumor-associated macrophages (TAMs) whose increased levels in HNSCC are associated with poor prognosis [ 12 , 117 ]. Also, stimulates the production of numerous cytokines by different cell types, such [ 116 ] as cancer-associated fibroblasts (CAFs), normal fibroblast, endothelial cells, neutrophils as well as oral dysplastic and cancer cells, among others [ 10 , 11 , 98 , 118 ], through an IL-1-dependent innate immune response.…”
Section: Il-1 Signaling In Head and Neck Squamous Cell Carcinomamentioning
confidence: 99%
“…This creates an inflammatory TME that can predispose to tumor progression [ 121 ] ( Figure 1 ). For example, in HNSCC IL-1 signaling drives neutrophil and monocyte recruitment [ 10 ], and accumulation of these tumor-associated leukocytes has been associated with poor prognosis [ 13 , 122 ]. The IL-1/IL-1R axis mediates chemokine release from normal tonsillar fibroblasts (NTF) induced by HPV-negative oropharyngeal carcinoma (OPC) cells, which can be reverted with IL-1 inhibition [ 11 ].…”
Section: Il-1 Signaling In Head and Neck Squamous Cell Carcinomamentioning
confidence: 99%
See 1 more Smart Citation
“…However, not all immune cell populations are enriched in HPV-positive tumors. Al-Sahaf and colleagues determined that HPV-negative tumors contain more neutrophils and express more of the neutrophil chemoattractant CXCL8 compared to HPV-positive tumors (15, 29). Overall, it is apparent that immune cell recruitment differs in HPV-positive vs HPV-negative tumors and that chronic inflammation could contribute to HPV-mediated carcinogenesis (30, 31).…”
Section: Discussionmentioning
confidence: 99%
“…Thirdly, in HPV-negative oropharyngeal squamous cell carcinoma (OPSCC), it has been demonstrated that the IL-1/IL-1R axis is responsible for the production of the chemokine CXCL8, which will recruit neutrophil cells to the TME. These tumor-associated neutrophil cells (TAN) are associated with poor prognosis in OPSCC [ 138 ].…”
Section: Role Of Il-1rap In Tumorsmentioning
confidence: 99%